Notes on the Herpetofauna of Kampung Giam, Padawan, Sarawak - Ramlah, Zainudin; Jennifer Ubung, Nawan; Marcie Elene, Marcus; Muhammad Fadzil Amram, Jopony; Nordianah, Nasip; Priscilla, Telon (BJRST Publisher, 2013)
Padawan lies at one of the proposed Sarawak Geopark, yet information on the herpetofauna of the area is limited. A survey was conducted from 16 August 2008 to 24 August 2008 to determine species assemblage and relative abundance of herpetofauna at Kampung Giam, Padawan. Sampling involved stream and forest transects, quadrat, pitfall and sticky traps at four study sites along Sungai Sewa. A total of 13 species of frogs (62 individuals), eight species of lizards (nine individuals) and four species of snake (one individual each) were captured. The area was dominated by the family of Ranidae (83.9%), followed by Bufonidae (8%), Dicroglossidae (3.2%), Microhylidae (3.2%) and Megophryidae (1.6%). The most abundant and dominant species was Odorrana hosii, with 36 individuals caught. In addition three endemic Bornean frogs namely Limnonectes leporinus, Meristogenys phaeomerus and Meristogenys orphnocnemis were also captured in this study, which account for 33.33% endemism. The reptiles caught, on the other hand, were relatively low with only 12 species and 13 individuals captured. Nevertheless this study provides an increment of Sarawak faunal database for conservation management of Bornean fauna as well as the Sarawak Geopark.